THE EFFECT OF MANAGERIAL OWNERSHIP, PRIVATE INSTITUTIONAL OWNERSHIP, STATE-OWNED INSTITUTIONAL OWNERSHIP AND PROFITABILITY TOWARDS DIVIDEND POLICY IN BANKING INDUSTRY - Irmadani, Uci; Prasetyo, Ahmad Danu (Journal of Business and Management, 2018)
This research aims to determine the effect of managerial ownership, private institutional ownership, state-owned institutional ownership and profitability towards dividend policy in banking industry. The research model uses dividend policy to reflect the agency issues and conflict of interests between agent (manager) and principle (shareholder). This research is categorized as causal comparative research. The sample of this research is bank companies listed in Indonesia Stock Exchange (IDX) from 2012-2016. The data needed for this research is collected from each company’s annual report available in idx.co.id. This research use data panel regression analysis method. The results of this research show that the managerial and private institutional ownership have negative and insignificant effect towards dividend policy in banking companies in Indonesia. The state-owned institution ownership has positive and significant effect towards dividend policy in banking companies in Indonesia. Profitability has positive and insignificant effect towards dividend policy in banking companies in Indonesia.